Prosumption, Networks and Value during a Global Pandemic: Lockdown Leisure and COVID-19. (3rd March 2021) - Bond, Alexander John; Widdop, Paul; Cockayne, David; Parnell, Daniel
Abstract: Following advances in information technology and the rise of social media, prosumption – a model of simultaneous production and consumption of the commodity – has become a significant focus in many industries and for academic study. Prosumption represents a new message creation and delivery paradigm, where anyone can seamlessly shift from consumer to contributor, to creator. Central to this is the idea of creating 'use-value' and re-orientating 'exchange value'. Perhaps an overlooked facet, but one deeply engrained in its manifestation is that prosumption is inherently relational, involving micro-interaction between consumer and producer. The recent global COVID-19 pandemic, it too being relational in its transmission, has had a paralysing effect on global leisure activities with households and sports organisations experiencing some form of state-enforced residential lockdown. Using social network analysis, this commentary examines the network structure of a prosumed leisure activity during societal lockdown and its implications for the leisure industries.